Wytyczne hetmana Wacława Rzewuskiego (1706-1779) dla służby pałacowej. Przyczynek do funkcjonowania rezydencji podhoreckiej w połowie XVIII wieku - Paduch, Katarzyna (Saeculum Christianum. Pismo Historyczne, 2019)
From 1729 the Palace in Podhorce was the residence of Grand Crown Hetman Waclaw Rzewuski (1709-1779). Hetman arranged a magnificent Old Polish magnate residence in the Podhorecki palace, having souvenirs of representatives of the Sobieski family and the Koniecpolski family, as well as a gallery of works of art, an armory and a library. This article is an attempt to present the functioning of the Podhorce residence in the light of the guidance kept in the Book of inventory and instructions of the Podhorce castle from 1745-1754. Among the preserved guidelines, one can distinguish instructions concerning various areas of the functioning of the Podhorce residence, namely: welcoming guests, the kitchen and the table of residence, security, heating and lighting of the palace, as well as the Podhorce stables.